A high-yielding strain of indole-3-acetic acid isolated from food waste compost metabolic pathways, optimization of fermentation conditions, and application - Fan, Yueqin (Environmental technology, 2023)
Food waste is a potential resource to prepare microbial fertilizer. However, functional microorganisms derived from the food waste compost (FWC) are relatively lacking. We have isolated, identified, characterized and optimized a high-yielding indole-3-acetic acid (IAA) strain from FWC and further evaluated its growth promoting effect on plants. A IAA high-yielding strain, Providencia sp.Y, with an initial IAA yield of 139.98 mg L-1, was obtained through high-throughput screening, and identified by 16S rRNA gene sequence. The novel strain Y may simultaneously involve the following three pathways from L-tryptophan to IAA, which were identified using liquid chromatography-tandem mass spectrometry: (1) L-tryptophan-indole-3-ethanol-indole-3-acetaldehyde-indole-3-acetic acid; (2) L-tryptophan-1-hydroxy-indole-3-ethanol-indole-3-acetic acid; (3) L-tryptophan-indole-3-acetamide-indole-3-acetic acid. The most suitable comprehensive conditions for IAA production, which were optimized by single factor experiment, were: culture time 12 h, inoculation amount 2% (v/v), NaCl concentration 4% (w/v), culture temperature 25℃, initial pH = 5, and L-tryptophan concentration 3.0 g L-1. The yield of IAA after optimization was increased by 590.48%, from 139.98 mg L-1 (before optimization) to 966.54 mg L-1. Diluted 200-fold microbial suspension could significantly improve the growth of pakchoi seedlings. The seedling plant height, root length, leaf width, leaf length, and fresh weight with microbial suspension increased by 17.39%, 107.35%, 77.98%, 37.75%, and 215.38%, respectively, compared with those without microbial suspension. The increase was greater than that of commercial bacterial agents. In conclusion, this isolated strain can be used as an economical microbial inoculant and provides a new germplasm resource for developing microbial fertilizers